Robô móvel suspenso por fio com pernas de comprimentos variáveis - Gonçalves, Rogério Sales (2006)
Some theoretical and experimental studies have been developed in order to produce independent equipment for inspection and maintenance of electric power and telecommunication transmition lines, increasing the process efficiency and reducing the risk of accidents with the employees who execute the task. This activity suits mobile robots because they are able to move avoiding existing obstacles on the cables. This study presents a mobile robot suspended by wire that is able to move along electric power and/or telecommunication transmition lines. Due to its variable length legs, it can avoid different types of obstacles placed at any position on wire, and for being suspended, your stability is guaranteed. The analyzed robot is constituted by a body and four legs with variable lengths. In this dissertation its kinematic model is presented and it has been proposed a methodology to enable the obstacle transposition. The study of the obstacles transposition is defined from the collision of the robot foot with the obstacle. Numerical, graphical simulation and experimental test results are presented to validate the proposed model.